2001
DOI: 10.1034/j.1600-0528.2001.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Dentists’ perceived stress and its relation to perceptions about anxious patients

Abstract: Dentists' perceptions about the stressfulness of dental practice, their perceptions about dental anxiety and its management were surveyed in a descriptive study. A mailed questionnaire was completed by 216 randomly selected Danish private dentists. Of these, nearly 60% perceived dentistry as more stressful than other professions. Dentist perceptions of the most intense stressors were (ranked): 1) running behind schedule, 2) causing pain, 3) heavy work load, 4) late patients and 5) anxious patients. Bivariate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(94 citation statements)
references
References 16 publications
5
89
0
Order By: Relevance
“…Similar results have been reported in studies of general dentists in the UK (68.4%), dentists in Denmark (59.7%) and orthodontists in Morocco (44%). 10,17,20 The most common stressors among general dentists in the current study were maintaining concentration, constant time pressures, concern over their ability to provide dental services in future and rising costs. Ayers et al reported consistent findings, in which the second and third most common sources of stress among general dentists in New Zealand were time-related pressure (48%) and the need to maintain high levels of concentration at work (43%); however, the most common source of stress was treating uncooperative children (52%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been reported in studies of general dentists in the UK (68.4%), dentists in Denmark (59.7%) and orthodontists in Morocco (44%). 10,17,20 The most common stressors among general dentists in the current study were maintaining concentration, constant time pressures, concern over their ability to provide dental services in future and rising costs. Ayers et al reported consistent findings, in which the second and third most common sources of stress among general dentists in New Zealand were time-related pressure (48%) and the need to maintain high levels of concentration at work (43%); however, the most common source of stress was treating uncooperative children (52%).…”
Section: Discussionmentioning
confidence: 99%
“…Similar questionnaires have been used in different studies all over the world. 9,11,16,17 The questionnaire was distributed to the participants for self assessment before being collected three days later.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, their assessment and prevention is an essential part of safety and overall quality of care. Anxiety and phobia in turn make the dentist's job hard and stressful (Moore and Brodsgaard, 2001; Hill et al, 2008), a fact leading to the idea, perhaps a myth, of a high suicide rate among professionals in the past years (Stein, 2004; Jones et al, 2016). …”
Section: Prevention Of Anxiety Pain and Emergencies In Dentistry: Bementioning
confidence: 99%
“…[47] Dentists indicated running behind schedule, causing pain, and heavy work load, late and anxious patients as well as being the most intense stressors in their work. [4748] Dentists, who reported that dental anxiety was primarily the result of general psychological problems in patients, usually had solo practices older than 18 years and reported high perceived stress. [47]…”
Section: Stressmentioning
confidence: 99%